Information Display Around Eyes Using the Vibration of SMA Wires and its Evaluation of Perceived Sensation - Song, Chunhao; Shigemune, Hiroki; Sawada, Hideyuki (2018 11th International Conference on Human System Interaction (HSI), 2018)
Shape-memory alloys (SMAs) are metal which have the shape memory effects. By forming them to thin wires, they can shrink at a certain temperature; and then extend to original length after cooling below this temperature, thus shape-memory effect is observed. When pulse current is applied to a SMA wire, Joule heat generated inside makes the wire shrink about 5% of its length, and returns to the origin length when the pulse stops, which generate vibration in accordance with the frequency of the current. A novel designed actuator using the vibration of two SMA wires is proposed in this paper. The actuator has compact size and low energy consumption of milliwatts order. Tactile sensation is one of the important ways in human's five senses, which are used to acquire information from surrounding environment. In this paper, we are trying to transmit recognized information by translating it to tactile sensation perceived by skin around eyes. We divide the skin area around eyes into 4 zones, and design two tactile display prototypes. By installing multiple actuators in prototypes and applying pulse signals with different parameters, we conduct experiments to find optimal driving parameters to generate tactile sensation in designated skin areas. The higher-level perception in these area is tested by combining different parameters and stimulation patterns. Finally, information transmission is evaluated by the feedback from subjects and it turns out the proposed system performs well. In the final part we also propose potential applications of this system.